Movement Disorders and the Gut: A Review. Issue 4 (5th February 2022) - Talman, Lauren S.; Pfeiffer, Ronald F.
Abstract: There is a close link between multiple movement disorders and gastrointestinal dysfunction. Gastrointestinal symptoms may precede the development of the neurologic syndrome or may arise following the neurologic presentation. This review will provide an overview of gastrointestinal accompaniments to several well‐known as well as lesser known movement disorders. It will also highlight several disorders which may not be considered primary movement disorders but have an overlapping presentation of both gastrointestinal and movement abnormalities.